PEMBERDAYAAN YAYASAN DISABILITAS BHAKTI SENANG HATI DALAM MENINGKATKAN PENDAPATAN DI DESA SIANGAN GIANYAR - Azis, Ita Silvia Azita; Amlayasa, Anak Agung Bagus; Nitiwidari, Dewa Ayu Putu; Ganawati, Nengah (UNIVERSITAS PGRI MADIUN, 2021)
Abstract. Difabel or disability is a term that includes interference, activity limitations, and participation restrictions. A disorder is a problem with the body's function or structure; An activity limitation is a difficulty faced by an individual in carrying out a task or action, while a participation restriction is a problem experienced by an individual in involvement in life situations. So disability is a complex phenomenon, reflecting the interaction between the characteristics of a person's body and the characteristics of the society in which he or she lives. This community partnership program aims to increase partners' entrepreneurial motivation and provide skills in the use of internet media to support product marketing functions in the form of proactive marketing strategies in order to increase life independence. The methods used in this service are: lectures, question and answer discussions, and demonstration methods for online marketing training programs. The result of this activity is that participants in this case people with disabilities who are under the Bhakti Happy Hati Gianyar Foundation are very enthusiastic about listening to counseling related to literacy and motivation to increase the entrepreneurial spirit and understand using social media applications as online marketing as an effort to increase life independence. Abstrak. Difabel atau disabilitas adalah istilah yang meliputi gangguan, keterbatasan aktivitas, dan pembatasan partisipasi. Gangguan adalah sebuah masalah pada fungsi tubuh atau strukturnya; suatu pembatasan kegiatan adalah kesulitan yang dihadapi oleh individu dalam melaksanakan tugas atau tindakan, sedangkan pembatasan partisipasi merupakan masalah yang dialami oleh individu dalam keterlibatan dalam situasi kehidupan. Jadi disabilitas adalah sebuah fenomena kompleks, yang mencerminkan interaksi antara ciri dari tubuh seseorang dan ciri dari masyarakat tempat dia tinggal. Program kemitraan masyarakat ini bertujuan untuk meningkatkan motivasi kewirausahaan mitra serta memberikan keterampilan dalam penggunaan media internet untuk menunjang fungsi pemasaran produk berupa strategi pemasaran yang proaktif agar dapat meningkaatkan kemandirian hidup. Metode yang digunakan dalam pengabdian ini adalah: ceramah, tanya jawab diskusi, dan metode demonstrasi untuk program pelatihan pemasaran online. Hasil kegiatan ini adalah peserta dalam hal ini penyandang disabilitas yang bernaung dibawah Yayasan Bhakti Senang Hati Gianyar sangat antusias mendengarkan penyuluhan berkaitan dengan literasi dan motivasi untuk meningkatkan jiwa kewirausahaan serta memahami menggunakan aplikasi media sosial sebagai pemasaran online sebagai upaya untuk meningkatkan kemandirian hidup.